About solubility of initial-boundary problem for a system of half-linear equations of magnetoelasticity - Botsenyuk О. M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
An existence theorem is obtained for the system of semilinear equations of magnetoelasticity. The asymptotic behavior of the solutions over time is established.